2018
DOI: 10.1186/s12957-018-1513-4
|View full text |Cite
|
Sign up to set email alerts
|

A quest for sphincter-saving surgery in ultralow rectal tumours—a single-centre cohort study

Abstract: IntroductionDespite the progress in the treatment of colorectal cancer, there is still no optimal strategy for tumours located adjacent to the anal sphincter. This study aims to evaluate oncological and functional results of surgery for rectal cancer in unfavourable locations in proximity to anal sphincters.Materials and methodsPatients with rectal cancer, which was either initially infiltrating the anal sphincter or located in the close proximity of the sphincter, were included in the study. Patients were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 52 publications
2
32
1
2
Order By: Relevance
“…Morbidity and mortality rates found in our study are similar to those reported by other authors, as well as to overall survival [23][24][25][26][27][29][30][31]36].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Morbidity and mortality rates found in our study are similar to those reported by other authors, as well as to overall survival [23][24][25][26][27][29][30][31]36].…”
Section: Discussionsupporting
confidence: 92%
“…There is no consensus concerning the indication of this procedure in regard to tumor distance from the anal verge. Various authors reported different indications in both cohort studies and review studies ranging from > 4cm to > 6cm from the anal verge [23,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies used the Wexner score to assess the level of continence ( Table 2); two others 36,44 used the Vaizey or Kirwin score. All studies that performed a preoperative assessment of function 32,39,41 confirmed that no major preoperative deviations in Wexner score were present. Summarizing data that reported Wexner scores at specific times (3, 6, 9, 12, 18, 24 months) showed a median Wexner score at 3 months of 9 (range 1-20) 38,41,43 .…”
Section: Continencementioning
confidence: 77%
“…and †median (range). The International Prostate Symptom Score (IPSS) ranges from 0 to 35, with categories no/mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) complaints. IIEF, International Index of Erectile Function; TaTME, transanal total mesorectal excision; n.r., not reported/not reported correctly; LapTME, laparoscopic total mesorectal excision.…”
Section: Faecal Incontinence Quality Of Life Scalementioning
confidence: 99%